Simulasi Perubahan Persyaratan Kredit Dalam Upaya Meningkatkan Laba - Felina Kusnakhin (Universitas Kristen Maranatha, 2019)
Financial management involves understanding and transferring assets and liabilities of the company, including freedom of use of profits, liability and debt, cash flow and profitability. Meanwhile every strategy exposes business people to trade-offs that present benefits and risks. Selling on credit is one of the strategies that helps companies to increase sales and maintain customer relationships, but on the other hand it presents the risk of billing. This research is intended to provide a solution to the problem of the duration billing.The research method used in this study is a descriptive study method. A research method todescribe the characteristics of people, events, or situations. In this study, the research object in question is CV. Y. The research began with calculating the effect of trade receivables on the company's financial statements, especially on the value of net cash increases. The study continued with a credit simulation of changes in credit terms by setting cash discounts, cash discount periods and payment limits. As for each credit terms of the simulation produces different effects on several costs associated. As for credit terms, too tight credit terms will cause a loss of sales and too loose credit terms will lead to bad expense. The simulation showed that every credit terms will lead to different profit projection. Overall, the results of the simulation research show that every credit terms will increase the profit. Keywords: Credit Terms, Sales on Credit, Profits